Gut microbiota dynamics in the weaner pig in response to experimental Escherichia coli challenge and dietary manipulation - Pollock, Jolinda (The University of Edinburgh, 2017)
The weaning transition period in pigs is linked to increased vulnerability to enteric disorders, which is partly attributed to destabilisation of the gut microbiota. Post-weaning colibacillosis is an economically important disease of the small intestine, which is most commonly caused by enterotoxigenic Escherichia coli (ETEC) strains. This disease has been variably linked to a diarrhoeal phenotype and decreased growth rate under clinical or sub-clinical conditions, and has been associated with shifts in particular bacterial populations using culturing methods. The emergence of next-generation sequencing technologies such as 16S rRNA gene metabarcoding now allows higher resolution study of complex microbial communities, without being reliant on the ability to culture fastidious micro-organisms. As part of this project, a 16S rRNA gene metabarcoding method was developed and validated to allow qualitative and quantitative measurement of gut microbiota shifts. A series of experimental ETEC challenge trials were carried out to monitor temporal faecal microbiota dynamics (Chapter 2), to further understand ETEC adhesion and shedding dynamics (Chapter 3) and to study potential changes in both ileal and faecal microbiota populations in response to dietary protein manipulation (Chapter 4). The effects of experimental treatments on pig health and performance were also measured as part of each experiment. Temporal shifts in ileal and faecal microbiota structure and stability were observed over the post-weaning period, as well as shifts in relative abundances of particular bacterial phylotypes (P < 0.05) (Chapter’s 2 and 4). ETEC challenge had no effects on faecal microbiota composition, pig health and performance when comparing to samples obtained from sham-challenged pigs (P > 0.05). However, when taking ETEC shedding level into account, variations in both microbiota structure and stability were observed at specific time points (P < 0.05) (Chapter 2). After a single-dose ETEC challenge, ETEC adhesion in the ileum and faecal shedding were evident up to 4 and 6 days post-challenge, respectively (Chapter 3). Changes in ileal microbiota structure and stability were observed in response to ETEC challenge (P < 0.05), with no changes exerted at faecal level (P > 0.05). Additionally, different dietary protein levels were linked to changes in ileal microbiota structure, stability and phylotype relative abundances (P < 0.05). Interestingly, significant differences in ileal microbiota structure were evident in samples obtained from ETEC-challenged pigs fed the low and high protein diets, with the pigs fed the high protein diet having significantly less stable ileal communities at population level (P < 0.05) (Chapter 4). The treatments had no effect on host performance (P > 0.05), but faecal consistency scores were higher in pigs fed the high protein diet (P < 0.05). In conclusion, both ETEC challenge and manipulation of dietary protein level had profound effects on ileal microbiota composition and faecal microbial communities were variable according to ETEC shedding status. These findings have implications for the development of alternative management strategies for enteric diseases in weaner pigs.
Keywords: weaner pig; colibacillosis; enterotoxigenic Escherichia coli; gut microbiota; protein levels